2017
DOI: 10.1016/j.molcel.2016.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Cas13b Is a Type VI-B CRISPR-Associated RNA-Guided RNase Differentially Regulated by Accessory Proteins Csx27 and Csx28

Abstract: SUMMARY CRISPR-Cas adaptive immune systems defend microbes against foreign nucleic acids via RNA-guided endonucleases. Using a computational sequence database mining approach, we identify two Class 2 CRISPR-Cas systems (subtype VI-B) that lack Cas1 and Cas2 and encompass a single large effector protein, Cas13b, along with one of two previously uncharacterized associated proteins, Csx27 or Csx28. We establish that these CRISPR-Cas systems can achieve RNA interference when heterologously expressed. Through a com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
444
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 478 publications
(467 citation statements)
references
References 40 publications
21
444
0
2
Order By: Relevance
“…For the type V effectors, the direct ancestors are difficult to identify, but different subfamilies of TnpB appear to have given rise to different subtypes, as indicated by sequence similarity and phylogenetic analysis (146, 147). The type VI effectors, Cas13, are unrelated to those in other CRISPR-Cas types and contain two HEPN (higher eukaryotes and prokaryotes nucleotide-binding) domains, which cleave RNA targets (1, 3, 149). As with type V effectors, the exact ancestors of these proteins are difficult to pinpoint, but it appears likely that either HEPN domain–containing Cas proteins of class 1 CRISPR-Cas systems, such as Csx6 and Csn1, or a distinct HEPN domain–containing toxin could be implicated (147).…”
Section: Adaptive Immunity: the Crispr-cas Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…For the type V effectors, the direct ancestors are difficult to identify, but different subfamilies of TnpB appear to have given rise to different subtypes, as indicated by sequence similarity and phylogenetic analysis (146, 147). The type VI effectors, Cas13, are unrelated to those in other CRISPR-Cas types and contain two HEPN (higher eukaryotes and prokaryotes nucleotide-binding) domains, which cleave RNA targets (1, 3, 149). As with type V effectors, the exact ancestors of these proteins are difficult to pinpoint, but it appears likely that either HEPN domain–containing Cas proteins of class 1 CRISPR-Cas systems, such as Csx6 and Csn1, or a distinct HEPN domain–containing toxin could be implicated (147).…”
Section: Adaptive Immunity: the Crispr-cas Systemmentioning
confidence: 99%
“…The recent comprehensive search for genomic loci that encode large proteins containing putative nuclease domains that could function as class 2 CRISPR-Cas effectors has revealed, arguably, the most direct links between microbial immunity and programmed cell death so far discovered (1, 146, 147, 149). Type VI effector proteins contain two HEPN domains predicted to possess RNase activity (146, 147).…”
Section: Interactions Between Defense Strategies: Coupling Between Immentioning
confidence: 99%
“…Three Cas13 protein families have been identified to date: Cas13a (previously known as C2c2), Cas13b, and Cas13c (12, 13). We recently reported that Cas13a enzymes can be adapted as tools for nucleic acid detection (14) as well as mammalian and plant cell RNA knockdown and transcript tracking (15).…”
Section: Introductionmentioning
confidence: 99%
“…The mature crRNA consists of a unique spacer of 25 to 65 bp in length (depending on the CRISPR-Cas type and subtype) flanked by portions of the adjacent repeats. In the third and final stage, interference, the effector Cas protein complex mediates recognition of the target DNA or RNA via base-pairing between the spacer and cognate protospacer, followed by cleavage of the target by Cas nucleases (19)(20)(21)(22)(23)(24).…”
mentioning
confidence: 99%